Azerbaijan's Strategic Position in the 'One Belt, One Road' Initiative: The Role of Baku Port, Alat Free Economic Zone and BTK Railway in Trade, Transport and Investment Relations with China - Khurshudov, Samir (My University, 2026)
Azerbaijan is a country rich in natural resources. Since gaining independence, the pace of national development has significantly accelerated. The country’s oil and gas reserves have attracted substantial foreign direct investment (FDI), particularly in the energy sector. The exploration and extraction of hydrocarbon resources have strengthened Azerbaijan’s financial capacity and enhanced its standing both domestically and internationally.1 To maintain balanced political relations with neighbouring countries and to mitigate potential obstacles in exporting oil and gas, Azerbaijan has diversified its export routes through the construction of multiple pipeline projects. These include the Baku-Novorossiysk Oil Pipeline, Baku-Supsa Oil Pipeline, Baku-Tbilisi-Ceyhan Oil Pipeline, Baku-Tbilisi-Erzurum Gas Pipeline, TANAP, and TAP. These pipelines have not only facilitated energy exports but also created opportunities to develop new infrastructure that supports the diversification of the economy and the growth of non-oil sectors2 . Azerbaijan’s strategic geographic position—located at the crossroads of East– West and North–South corridors—adds significant value to its involvement in regional and global transportation initiatives. The country actively participates in major projects such as the Middle Corridor, the Trans-Caspian International Transport Route (TITR), the Transport Corridor Europe-Caucasus-Asia (TRACECA), the Trans-Caucasus Trade and Transit Corridor (TCTC), and the Belt and Road Initiative (BRI). These trade routes play a vital role in enhancing economic connectivity, particularly between distant markets, and offer important opportunities to strengthen various sectors of the national economy3 .
Keywords: Transportation -- Economic aspects.; Railroads -- Economic aspects.; Ports and harbors -- Economic aspects.; Azerbaijan -- Economic relations -- China.; Caucasus -- Commerce.; Freight and freightage.